Butyrate promotes slow-twitch myofiber formation and mitochondrial biogenesis in finishing pigs via inducing specific microRNAs and PGC-1α expression1. (22nd June 2019) - Zhang, Yong; Yu, Bing; Yu, Jie; Zheng, Ping; Huang, Zhiqing; Luo, Yuheng; Luo, Junqiu; Mao, Xiangbing; Yan, Honglin; He, Jun; Chen, Daiwen
Abstract: The present study aimed to investigate the influence of dietary butyrate supplementation on muscle fiber-type composition and mitochondrial biogenesis of finishing pigs, and the underlying mechanisms. Thirty-two LY (Landrace × Yorkshire) growing pigs with BW of 64.9 ± 5.7 kg were randomly allotted to either control (basal diet) or butyrate diets (0.3% butyrate sodium). Compared with the control group, diet supplemented with butyrate tended to increase average daily gain ( P < 0.10). Pigs fed butyrate diet had higher intramuscular fat content, marbling score and pH24 h, and lower shear force and L * 24 h in longissimus thoracis (LT ) muscle than that fed control diet ( P < 0.05). Interestingly, supplemented with butyrate increased ( P < 0.05) the mRNA level of myosin heavy chain I (MyHC-I) and the percentage of slow-fibers, and decreased ( P < 0.05) the mRNA level of MyHC-IIb in LT muscle. Meanwhile, pigs in butyrate group had an increase in mitochondrial DNA (mtDNA) copy number and the mRNA levels of mtDNA-encoded genes ( P < 0.05). Moreover, feeding butyrate diet increased PGC-1α (PPAR γ coactivator 1α) level, decreased miR-133a-3p level and increased its target gene level (TEAD1, TEA domain transcription factor 1), increased miR-208b and miR-499-5p levels and decreased their target genes levels (Sp3 and Sox6, specificity protein 3 and SRY-box containing gene 6; P < 0.05) in the LT muscle. Collectively, these findings suggested that butyrate promoted slow-twitch myofiber formation and mitochondrial biogenesis, and the molecular mechanism may be via upgrading specific microRNAs and PGC-1α expression, finally improving meat quality.